Polyaluminium chloride basic material, dynamic water balance wet sterilization dressing and preparation method thereof
By using particulate liquid dressing prepared by polymer alkali aluminum chloride and wet sterilization dressing with dynamic water to form a dynamic water balance, the problem of existing dressings being difficult to prevent infection and achieve automatic water balance on wounds is solved, and the wound is sterile, moist and dynamic balanced.
Patent Information
- Application Number
- CN202410836326.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-06-26
AI Technical Summary
It is difficult for existing dressing technology to have both high-efficiency anti-infection function and automatic water balance function of wounds, resulting in infection and passive dehydration of wounds after using dressings.
Polypolymerized alkali aluminum chloride is used as the main material of the dressing, and it is converted into a particulate liquid form through a specific preparation method, and a wet sterilized dressing with dynamic water balance is formed in combination with deionized water. This material has hygroscopicity and efficient ability to adsorb hydrophilic biological infectious substances, and can form a continuous aqueous film layer on the wound surface to achieve dynamic equilibrium.
It achieves a sterile, moist and dynamic balanced environment on the wound, effectively preventing infection and alleviating the pain caused by passive dehydration of the wound, and at the same time has the ability to effectively adsorb and isolate microorganisms.
Smart Images

Figure CN118791029B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dressings, in particular to a polybasic aluminum chloride, dynamic water balance wet sterilization dressing and a preparation method thereof. Background Art
[0002] Dressings are isolation materials applied to the wound surface after a body surface trauma occurs. Since the establishment of microbiology, the function of dressings is mainly to isolate infectious pathogens in the environment, obtain an infection-free wound surface, and provide a basic physical barrier for the wound surface to prevent secondary trauma or aggravation of trauma. Commonly used dressing products are rich in variety and are generally composed of a variety of functional materials, including fiber textile materials, hydrogel materials, liquid film-forming materials, antibacterial and antibacterial materials, and so on.
[0003] Existing dressing products can be roughly divided into two categories: hydrophilic isolation and hydrophobic isolation. The material matrix of hydrophilic isolation products is hydrophilic and has high tissue affinity. It directly contacts the wound tissue and can even become a tissue scaffold structure during the wound healing process. Typical materials include collagen hydrogel dressings; such materials generally do not have antibacterial properties and need to add antibacterial materials to form a functional complex, which cannot prevent the passive dehydration of the wound. Hydrophobic isolation materials are more widely used and have long been the main clinical dressing tool. Hydrophobic isolation dressings are generally made of oily materials as hydrophobic functional materials, directly covering the wound or compounding with carrier materials, such as cotton pads loaded with vaseline, animal fats, beeswax and other materials. Hydrophobic dressings can partially isolate the source of infection in the environment and reduce the passive dehydration of the wound. Physiologically, the source of pain from surface trauma, in addition to the pain caused by physical damage to the tissue caused by the trauma, mainly includes infection and passive dehydration of exposed tissue. When a body surface injury occurs, one of the current clinical medical regulations is to prohibit the wound surface from contacting with water; preventing the wound from getting wet is also a common sense and even a rule of life that has long been widely accepted. Existing dressing technologies and products cannot simultaneously have high-efficiency infection prevention functions and wound surface automatic water balance functions.
[0004] Achieving a permanently moist, non-infected wound with a dynamic water balance will be a substantial advancement in dressing technology and product direction, and may also be a substantial advancement in infection prevention technology in a broad sense. Summary of the invention
[0005] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a polyaluminium chloride, a dynamic water balance wet sterilizing dressing and a preparation method thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing polyaluminium chloride, comprising the following steps:
[0007] (1) After uniformly mixing mixed crystalline fumed alumina nanopowder and deionized water, a chlorine source material is added to obtain a first reactant; wherein the molar ratio of aluminum element to chlorine element is (0.9-1):3; and the mass ratio of deionized water used to disperse the alumina powder to the alumina powder is (4.5-5.0):1;
[0008] (2) heating the first reactant to boiling at a standard atmospheric pressure, evaporating and reducing the volume until the entire reactant is foamed, and heating the foaming material at 100-110° C. until there is no free water, thereby obtaining a second reactant;
[0009] (3) The second reactant is diluted to 1 liter with deionized water, stirred and mixed, and then centrifuged to remove the precipitate to obtain a third reactant; the third reactant is a light yellow clear sol system, which is a polybasic aluminum chloride (〔Al2(OH) n Cl (6-n) 〕 m ), a clear sol system consisting of residual chlorine source material, alumina crystal particles and water;
[0010] (4) heating the third reactant to boiling at a standard atmospheric pressure, maintaining the boiling state until a film appears on the surface of the system, the system becomes turbid, and after bubbling again, stopping the heating to obtain a bright orange system;
[0011] (5) allowing the bright orange system to stand or centrifuge to remove the precipitate to obtain a yellow, clear, and thick matrix product, namely, the polyaluminium chloride.
[0012] The present invention provides a granular liquid polybasic aluminum chloride, which is infinitely miscible with water and maintains a particle form. The advantages of the polybasic aluminum chloride described in the present invention are as follows: (1) The granular liquid polybasic aluminum chloride is hygroscopic, and the water content of the material changes with the relative humidity and temperature of the air when the material is in liquid state, and maintains a dynamic balance with the environment. The boiling point of the material is higher than the boiling point of water, and it does not evaporate under normal temperature conditions on the surface. (2) The granular liquid polybasic aluminum chloride has strong hygroscopicity under common natural environments on the surface, and the particles are filled and connected by water molecules to form a continuous aqueous film layer. The particle size is normally distributed in the range of 0.01-4.0 μm, and it is easy to form a densely stacked dynamic multi-layer particle structure. Under ordinary surface habitable environments, the granular material accumulates on the wound surface to form a viscous flexible isolation layer, and the layer thickness can be dynamically maintained at about 5-100 μm. The viscous flexible film layer is conformable, allowing different parts of the wound surface to have relative displacement and maintaining the integrity of the film layer. (3) The melting point of the liquid high-polymer basic aluminum chloride granular material is about -150°C. Under current technical conditions, it is difficult to directly measure the specific surface area of the water-soluble liquid micro-nano granular material. According to the normal distribution data of the particle size, the liquid high-polymer basic aluminum chloride granular material has a specific surface area greater than 50㎡ / cm3. The liquid basic aluminum chloride granular material has a highly efficient adsorption effect on hydrophilic biological invaders, and forms a complex with the hydrophilic invader particles to prevent the invaders from invading the wound base.
[0013] Preferably, in the step (1), the mass percentage of each crystal form in the mixed crystal fumed alumina nanopowder determined by XRD is as follows: the mass percentage of the θ crystal form is approximately 79.71%, the mass percentage of the α crystal form is 0.1014%, the mass percentage of the γ crystal form is approximately 19.97%, and the mass percentage of the η crystal form is 0.227%; the average particle size of the mixed crystal fumed alumina nanopowder is 4-5 μm; and the chlorine source material is at least one of hydrogen chloride and titanium chloride.
[0014] Further preferably, the average particle size of the mixed crystal fumed alumina nanopowder is 4.43016 μm; and the chlorine source material is hydrogen chloride.
[0015] Preferably, the average particle size of the polyaluminium chloride is 105-115 nm, the D50 particle size is 340-360 nm, and the D90 particle size is 3630-3650 nm; preferably, the average particle size of the polyaluminium chloride is 111.8 nm, the D50 particle size is 349 nm, and the D90 particle size is 3640 nm.
[0016] Preferably, the particle size detection result of the polyaluminium chloride basic according to the present invention is obtained by testing the particle size distribution laser diffraction method according to GB / T19077-2016.
[0017] The invention provides granular liquid polyaluminium basic chloride prepared by the preparation method of polyaluminium basic chloride.
[0018] The invention provides application of the polymeric basic aluminum chloride in preparing a dynamic water balance wet sterilization dressing.
[0019] The invention provides a dynamic water balance wet sterilization dressing, comprising the following components: the polyaluminium chloride and deionized water; the volume fraction of the polyaluminium chloride is 10-20%.
[0020] The invention provides a dynamic water balance wet sterilization dressing, comprising the following components: the polyaluminium chloride, oxide powder and deionized water; the volume fraction of the polyaluminium chloride is 2.0-5.0%.
[0021] Preferably, the oxide powder is at least one of titanium oxide, zinc oxide, aluminum oxide and bismuth oxide.
[0022] The present invention further provides a method for preparing the dynamic water balance wet sterilization dressing, comprising the following steps: dissolving polybasic aluminum chloride in deionized water, and obtaining the dynamic water balance wet sterilization dressing after constant volume.
[0023] The present invention further provides a method for preparing the dynamic water balance wet sterilizing dressing, comprising the following steps:
[0024] S1, dissolving polyaluminium chloride in deionized water, adding oxide powder, and mixing well to obtain a clear and transparent dressing matrix;
[0025] S2, dissolving the dressing matrix in deionized water, adding the titanium oxide powder dispersed in deionized water, and fixing the volume to 1 liter with deionized water to obtain the dynamic water balance wet sterilization dressing.
[0026] The present invention uses granular liquid high-poly basic aluminum chloride as the matrix of the dressing combination, uses water as a dispersant, and adds oxide powder to form a dynamic water balance wet sterile dressing. The material obtained by directly mixing the matrix material and deionized water in proportion is also a high-efficiency dressing product, and there is no need to add other oxide particles as functional enhancement components. The above-mentioned dressing matrix is the product of a specific process, and forms a stable sol with water. The particle size range of the colloid particles is about 10-4000 nanometers, and it can form a uniform, complete, and continuous aqueous film layer on the surface of the skin and the surface of the exposed wound tissue, and the film layer thickness is greater than 10μm. The matrix always remains saturated with water under ordinary surface conditions, and the water content changes automatically with changes in parameters such as ambient temperature, humidity, and air pressure. The matrix is prepared by continuous hydrolysis, polymerization, and purification processes. Using gas phase nano-alumina powder as the aluminum source, introducing chlorine source material, reacting in a boiling water environment at normal pressure, and removing impurities twice, a granular liquid polybasic aluminum chloride with a high degree of polymerization is obtained. The polymer can form a stable and homogeneous solution with water. The polybasic aluminum chloride in the solution maintains a granular state. A specified amount of oxide particles can be added to the solution to form a sol without precipitation.
[0027] The interaction between the polymerized basic aluminum chloride of the present invention and the wound surface is an important link in realizing the function of the dressing. On the one hand, fresh wounds after serum-stopping wounds (open wounds, skin damage, tissue exposure) contain tissue exudates, transudates, serum, electrolytes, and easily cross-linked hydrophilic proteins, peptides and other substances, which can easily form aqueous complexes with the basic aluminum chloride of the present invention. The aqueous complex forms an inert isolation layer on the wound surface. On the other hand, the surface of the basic aluminum chloride particles of the present invention is a water film layer, which does not induce immune recognition. The aqueous complex formed with the wound exudate is deposited and adhered on the surface of the fresh wound, forming a physiological inert isolation layer without immune recognition effect; the inert isolation layer solidifies on the surface of the active tissue at the base of the wound due to the inherent immunity and metabolism of the tissue, forming a dense inert isolation layer, which can be considered as a pseudo-skin isolation tissue; the newly added liquid high-polymer basic aluminum chloride film layer on the inert isolation layer, and the composite structure composed of the base inert layer, ensure that there is no biological infection invading the base layer of the active physiological tissue at the wound, and will not cause infection.
[0028] The present invention also provides application of the dynamic water balance wet sterilization dressing in the field of medical devices and medical consumables.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Dynamic water balance wet sterilization dressing, which is an oxide quantum dot hydrosol composite material, which directly acts on the surface of the wound tissue to form a tissue denaturation isolation film, and the hydrosol material added to the film for the second time evaporates and dehydrates naturally to form a sterilized water film structure. The structure maintains a dynamic balance of water content in an open environment, and the oxide quantum dot material contained in the film has a photothermal catalytic sterilization function, thereby obtaining a permanently moist sterile wound. The wet sterile wound has no infection and no passive dehydration of the adjacent tissues of the wound, which can greatly reduce pain and achieve the goal of reliable sterile and painless wound management. As a wound dressing, this type of material does not induce drug resistance, does not distinguish the biological type and state of the infection source, is not consumed and lost due to the sterilization process, is not absorbed by the tissue, and remains physiologically inert and non-toxic, and has the same extremely high adsorption, isolation and killing efficiency for infections of all biological types and states (including spores). (2) The principle of dynamic water balance achieved by this material in the air is related to the hygroscopicity of chloride salts. This material is applied to animal husbandry or human body as a direct aqueous dressing for aseptic management and water balance management of surface wounds. No bandaging is required and the wound is painless. This material can be used for large-scale population epidemic prevention and can efficiently kill microbial pathogens from any infectious environmental source, including spores, sporozoites, bacteria, viruses, molds, mycoplasmas, etc., without inducing drug resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a microscopic morphology image of the finished substrate prepared in Example 1;
[0031] Figure 2 The DLS nanoparticle size distribution diagram, where (a) is the particle size-particle number fraction curve; (b) is the particle size-particle volume fraction curve; (c) is the particle size-light scattering intensity fraction curve;
[0032] Figure 3 These are pictures of mice recovering after back skinning surgery, where (a) is a picture of mice recovering 6 hours after surgery; (b) is a picture of mice recovering 24 hours after surgery; (c) is a picture of mice recovering 36 hours after surgery; (d) is a picture of mice recovering 48 hours after surgery; and (e) is a picture of mice recovering 80 hours after surgery. DETAILED DESCRIPTION
[0033] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. In the embodiments, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0034] In the mixed crystal alumina nanopowder used in the present invention, the mass percentage of each crystal form is as follows: the mass percentage of the θ crystal form is about 79.71%, the mass percentage of the α crystal form is 0.1014%, the mass percentage of the γ crystal form is about 19.97%, and the mass percentage of the η crystal form is 0.227%; the mass percentage of the above-mentioned crystal forms is the manufacturer's factory inspection data, the conditions of batch production will have slight fluctuations, and there will be corresponding differences in the inspection of each batch of finished products.
[0035] Example 1
[0036] 1. Prepare the materials: Take 100 g of mixed crystal fumed alumina nanopowder, 1 liter of 6 mol / L hydrogen chloride aqueous solution, and 500 ml of deionized water.
[0037] 2. Dissolution and acidification: After fully mixing the alumina powder and purified water, stir and add hydrochloric acid to obtain the first reactant.
[0038] 3. Cracking and polymerization reaction: The first reactant is heated to boiling under a standard atmospheric pressure, and the volume is reduced by boiling and evaporation until the whole reactant foams, and the foaming material is heated at 100-110°C until there is no free water.
[0039] 4. First impurity removal. The reaction system that has completed the cracking and polymerization reaction is diluted to 1 liter with deionized water, stirred and mixed, and then centrifuged to remove the precipitate to obtain a light yellow clear liquid, completing the first impurity removal. The obtained product is polyaluminum chloride (〔Al2(OH) n Cl (6-n) 〕 m ), a light yellow clear sol system composed of residual hydrogen chloride, aluminum oxide crystal particles and water.
[0040] 5. Acid removal and purification reaction. The obtained hydrosol system is heated to boiling under a standard atmospheric pressure, and the boiling state is maintained until a film appears on the surface of the hydrosol system, the system becomes turbid, and foaming occurs again, and then the heating is stopped.
[0041] 6. Second impurity removal: The reaction system that is bright orange after the acid removal and purification reaction is allowed to stand or centrifuge to remove the precipitate to obtain a yellow, clear, thick matrix product.
[0042] The subsequent dressing preparations are all based on the preparation of 1 liter of dressing products as an example.
[0043] Application Example 1 (Preparation of Finished Dressing with Other Oxide Particles Added)
[0044] 1. Prepare the materials: Take 20 g of the polymer matrix prepared in the previous step, 0.8 g of zinc oxide powder with an average particle size of about 30 nanometers, 0.8 g of titanium oxide powder with an average particle size of 3-5 nanometers, and 1 liter of deionized water.
[0045] 2. Prepare the dressing matrix. Add deionized water to the polymer matrix and adjust the volume to 150 ml; add zinc oxide powder and mix well to obtain a clear and transparent dressing matrix.
[0046] 3. Volume adjustment. Add deionized water to the dressing matrix and adjust the volume to 800 ml; disperse the titanium dioxide powder in deionized water and adjust the volume to 100 ml. Mix the obtained titanium dioxide sol with the dressing matrix sol, add deionized water and adjust the volume to 1 liter to obtain the finished dressing.
[0047] Application Example 2 (Preparation of finished dressing without adding other oxide particles)
[0048] 1. Take 100 ml of the polymer matrix prepared in the previous step;
[0049] 2. Add deionized water and make up to 1 liter.
[0050] Performance Test 1 Microscope observation.
[0051] Test method: Take 10% by volume of the finished dressing product, i.e., the finished dressing product of Application Example 2 without adding other oxide particles, and observe it under an inverted microscope at a magnification of 800 times.
[0052] Test results: The results are as follows Figure 1 As shown, Figure 1 This is a microscopic morphology of the finished matrix prepared in Example 1. The morphology that can be visually distinguished under the microscope is micron-sized particles, which are dispersed and less agglomerated.
[0053] Performance Test 2DLS Nanoparticle Size Distribution.
[0054] Test method: Refer to GB / T 19077-2016 "Particle size distribution laser diffraction method".
[0055] Test results: Figure 2 The DLS nanoparticle size distribution diagram, where (a) is the particle size-particle number fraction curve; (b) is the particle size-particle volume fraction curve; (c) is the particle size-light scattering intensity fraction curve;
[0056] The average particle size of the polyaluminium chloride is 111.8 nm, the PDI polydispersity index is 0.93, the D5 particle size is 14 nm, the D10 particle size is 16.9 nm, the D50 particle size is 349 nm, and the D90 particle size is 3640 nm.
[0057] Performance Test 3
[0058] Test method: The mouse back skinning surgery was performed in an open indoor environment without artificial clean conditions. All subsequent breeding and observation experiments were carried out in an open indoor environment. No antibiotics, antiviral drugs, or antifungal drugs were used, and the environment was not disinfected or sterilized, etc.
[0059] Immediately after surgery, the wound was rinsed and covered with a 10% volume fraction water-balanced sol dressing (basic dressing), and 2.0 ml of dressing was added every 12 hours. No water was used to clean the wound during the entire process.
[0060] Test results: The observations obtained are as follows Figure 3 shown.
[0061] Figure 3 These are pictures of mice recovering after back skinning surgery, where (a) is a picture of mice recovering 6 hours after surgery, with no visible infection; (b) is a picture of mice recovering 24 hours after surgery, with no visible infection; (c) is a picture of mice recovering 36 hours after surgery, with no visible infection; (d) is a picture of mice recovering 48 hours after surgery, with no visible infection; and (e) is a picture of mice recovering 80 hours after surgery, with no visible infection.
[0062] Performance Test 4
[0063] Test method: 10% volume fraction of granular liquid high-poly aluminum chloride aqueous solution, in accordance with the Ministry of Health of the People's Republic of China 2002 edition of the "Disinfection Technical Specifications" to perform antibacterial efficiency test. Pathogen materials used: Staphylococcus aureus, Candida albicans, polio virus (PV-Ⅰ vaccine strain).
[0064] Test results: The antibacterial efficiency data obtained are shown in Table 1.
[0065] Table 1
[0066]
[0067]
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing granular liquid polybasic aluminum chloride, characterized in that: The steps include: (1) After uniformly mixing mixed crystalline fumed alumina nanopowder and deionized water, a chlorine source material is added to obtain a first reactant; wherein the molar ratio of aluminum element to chlorine element = (0.9-1):3; the mass ratio of deionized water used to disperse the alumina powder to the alumina powder = (4.5-5.0):1; the mass percentage of each crystal form in the mixed crystalline fumed alumina nanopowder is as follows: the mass percentage of the θ crystal form is 79.71%, the mass percentage of the α crystal form is 0.1014%, the mass percentage of the γ crystal form is 19.97%, and the mass percentage of the η crystal form is 0.227%; (2) heating the first reactant to boiling at a standard atmospheric pressure, evaporating and reducing the volume until the entire reactant is foamed, and heating the foaming material at 100-110° C. until there is no free water, thereby obtaining a second reactant; (3) adding deionized water to the second reactant to a fixed volume, stirring and mixing, and then centrifuging to remove the precipitate to obtain a third reactant; (4) heating the third reactant to boiling at a standard atmospheric pressure, maintaining the boiling state until a film appears on the surface of the system, the system becomes turbid, and after bubbling again, stopping the heating to obtain a bright orange system; (5) allowing the bright orange system to stand or centrifuge to remove the precipitate to obtain a yellow, clear, and thick matrix product, namely, the polyaluminium chloride.
2. The method for preparing polyaluminium chloride as claimed in claim 1, characterized in that: In the step (1), the average particle size of the mixed crystal fumed alumina nanopowder is 4-5 μm; and the chlorine source material is at least one of hydrogen chloride and titanium chloride.
3. The method for preparing polyaluminium chloride according to claim 1, wherein: The average particle size of the polyaluminium chloride is 105-115 nm, the D50 particle size is 340-360 nm, and the D90 particle size is 3630-3650 nm.
4. A polyaluminium chloride prepared by the method for preparing polyaluminium chloride as claimed in any one of claims 1 to 3.
5. Use of the polyaluminium chloride as claimed in claim 4 in the preparation of a dynamic water balance wet sterile dressing.
6. A dynamic water balance moist sterilizing dressing, characterized in that: The invention comprises the following components: the polyaluminium chloride according to claim 4 and deionized water; the volume fraction of the polyaluminium chloride is 10-20%.
7. A dynamic water balance moist sterilizing dressing, characterized in that: The invention comprises the following components: the polyaluminium chloride according to claim 4, oxide powder and deionized water; the volume fraction of the polyaluminium chloride is 2.0-5.0%; the oxide powder is at least one of titanium oxide, zinc oxide, aluminium oxide and bismuth oxide.
8. A method for preparing the dynamic water balance moist sterilizing dressing according to claim 6, characterized in that: The method comprises the following steps: dissolving polybasic aluminum chloride in deionized water, and obtaining the dynamic water balance wet sterilization dressing after constant volume.
9. A method for preparing the dynamic water balance moist sterilizing dressing according to claim 7, characterized in that: The steps include: S1, dissolving polyaluminium chloride in deionized water, adding oxide powder, and mixing well to obtain a clear and transparent dressing matrix; S2, dissolving the dressing matrix in deionized water, adding the oxide powder dispersed in deionized water, and fixing the volume with deionized water to obtain the dynamic water balance wet sterilization dressing.
10. Use of the dynamic water balance wet sterilization dressing according to claim 6 or 7 in the field of medical devices and medical consumables.
Citation Information
Patent Citations
Wet wound surface dressing and preparation method thereof
CN102847196A
Preparation method of anhydrous neodymium chloride
CN104944459A
Process for preparing sulfate-containing basic solutions of polyaluminumchloride
US6241958B1